PENGARUH UKURAN PERUSAHAAN TERHADAP RETURN YANG DIMODERASI OLEH PERTUMBUHAN LABA PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Saputri, Marlinda (Komunitas Manajemen Kompetitif, 2018)
The purpose of this study was to determine the effect that size company, which is moderated by profit growth on return (rate return) shares. The study population is a registered banking companyon the Indonesia Stock Exchange (IDX). The sample used purposive sampling method with criteria for banking companies and issuing complete financial statements research period, and have a positive share equity. Based on the criteria obtained a sample of 20 companies. The data used is the secondary data obtained from financial statements and obtained from the Indonesian Capital Market of Directory 2013-2017. Hypothesis testing is carried out using quantitative analysis methods through multiple regression models and t-statistical tests. Based on processing results seen that the size of the company does not have a significant effect on stock returns with the size of the company, which is moderated by profit growth has no effect significant to stock returns.